Comparative Analysis of the Cloud Behavior over Inland and Coastal Regions within Single Climate Characteristics - Sanghee Lee; Sug-Whan Kim; Seung-On Hwang; Ji Nyeong Choi; Ki-Beom Ahn; Jinho Kim (Atmosphere, 2020)
Continuous and accurate ceilometer measurements can provide the sky-condition such as cloud base height (CBH), cloud vertical structure (CVS), and cloud cover at around the sites of meteorological stations. In this study, ceilometer measurement data over a period of 3 years (January 2017 to December 2019) were analyzed to compare the characteristics of CBH at inland and coastal stations sharing the same climate characteristics in Korea. The annual averaged frequency of cloud occurrence between 0 and 7750 m at the first CBH is similar in both inland (41.8 ± 10.2%) and coastal (40.3 ± 9.5%) areas. However, there are differences in monthly and seasonal trends. The maximum cloud occurrence appears in summer (winter) of 64.3% (60.1%) in inland (coastal) areas, while the minimum of 25.6% (21.9%) shows in transient seasons of spring and autumn. In winter, the cold surge of northwest wind tends to increase the cloud occurrence from the ocean at coastal rather than in the inland area. It is shown that monthly cloud occurrence in each station is closely related to its monthly precipitation variation. The CVS frequency calculated from the total number of CBH with 250 m vertical bins shows the maximum between 500 to 1500 m (0 to 1000 m) in inland (coastal) areas, indicating more frequent occurrence at a lower height in the coastal area. It is mainly caused by the seasonal variability of the low-level clouds in the coastal region, which occurs two to three times higher in spring and summer than in other seasons. The study implies that long-term measurements of ceilometer would provide a better understanding of the characteristics of cloud behaviors in inland and coastal areas.